Assessment of Quality of Strategic Documents of Development of the Financial Market and Its Segments - Yury Alekseevich Danilov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
This article presents an analysis of the quality of the 13 strategic documents in the field of development of the financial sector of the Russian Federation and its branches, developed and adopted during 2001-2016. As the quality criteria have been used 5 principles of strategic planning, enshrined in the Federal Law «On the strategic planning» and 4 factors in the successful programs of reform of the financial sector in the countries - competitors of Russia in the global financial markets. Based on the analysis conclusions were drawn about the poor quality of the processes of strategic planning of the financial sector in the Russian Federation, given the cause-and-effect relationship between the disparity to different criteria (failure to realistic objectives as a whole because of the lack of responsibility), were made on the bottom of the analysis revealed other common disadvantages of strategic documents in this area.